Family Planning of HIV-Infected Women in Bumrasnaradura Infectious Disease Institute - ลิ้มปัญญาเลิศ ปิยวรรณ (Disease Control Journal, 2011)
This report was a study of family planning among women infected with HIV in Bamrasnaradura Infectious Diseases Institute. During October and December 2010, there were 331 cases of women infected with HIV in reproductive age 16-49 years. The average age was 36.80 years old which was older than the age reported by Thai epidemiological study in women infected with HIV. The study found that around73.9% of this group of women still had sexual partner with regular sexual activity. About 73.8% of thepatients were receiving family planning services, and 73.9 % were receiving contraception of which 93.6%using condom. About 27.4 per cent of the patients wanted to have children. In conclusion, it was recommended that medical personnel should provide regularly family planning services for women infected withHIV to prevent unwanted pregnancy or other complication such as vertical transmission of HIV.